1991
DOI: 10.1111/j.1365-2605.1991.tb01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of sperm angiotensin converting enzyme in fertilization

Abstract: Recently it has been observed that ejaculated human sperm possess high angiotensin converting enzyme (ACE) activity and that this enzyme is released during the process of capacitation. This observation raises the possibility that ACE may be involved in the fertilization process. To verify this hypothesis, we tested the effects of a potent ACE inhibitor, Captopril, on acrosome reaction induced by capacitating medium (3.5% HSA-added BWW) and on ability of human capacitated spermatozoa to penetrate zona-free hams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…A role of the tACE in capacitation has been suggested by several authors (211,658). Previous reports have suggested that ACE is released during sperm capacitation (356), which was confirmed after exposure to ACE inhibition that affected the acrosome reaction and the ability of human sperm to penetrate an egg (212).…”
Section: Male Reproductive Tractmentioning
confidence: 86%
“…A role of the tACE in capacitation has been suggested by several authors (211,658). Previous reports have suggested that ACE is released during sperm capacitation (356), which was confirmed after exposure to ACE inhibition that affected the acrosome reaction and the ability of human sperm to penetrate an egg (212).…”
Section: Male Reproductive Tractmentioning
confidence: 86%
“…A previous study has shown that spontaneous capacitation, acrosomal reaction, and premature capacitation of frozen-thawed spermatozoa are inhibited by ACE inhibitors (Foresta et al 1991), which indicates that ACE may also be an important factor for premature capacitation in frozen-thawed sperm. The levels of ACE on the surface of spermatozoa have been shown to be inversely proportional to their fertilization capacity (Kohn et al 1998, Shibahara et al 2001.…”
Section: Proteins Related To Premature Capacitationmentioning
confidence: 94%
“…Angiotensin II is not the only RAS component ascribed with functionality in the testicular RAS. Recent studies have established that Ang (1-7) activation of the Mas receptor is necessary for spermatogenesis in mice and rats [37] and that testicular ACE is necessary for capacitation and subsequent fertilization [38][39][40][41][42]. Thus, this novel Ang II/Ang III binding site could participate in Ang II-regulated male reproductive functions.…”
Section: Tissue Distributionmentioning
confidence: 99%